Black–White Disparities in Disability Among Older Americans: Further Untangling the Role of Race and Socioeconomic Status - Fuller-Thomson, Esme (2009)
OBJECTIVES: To explore the impact of adjusting for income and education on disparities in functional limitations and limitations in activities of daily living (ADLs) between Black and White older Americans. METHOD: Data from the 2003 American Community Survey were used to examine the associations of education and income, stratified by race and gender, with functional limitations and ADLs, in a sample of 16,870 non-Hispanic Blacks and 186,086 non-Hispanic Whites aged 55 to 74. Sequential logistic regressions were used to examine the relative contribution of income and education to racial disparities. RESULTS: Ninety percent of the Black–White difference in disability rates for men and 75% of the difference for women aged 55 to 64 were explained by income and education. DISCUSSION: The greatly elevated risk of disability among Blacks aged 55 to 74 is largely explained by differences in socioeconomic status. Reductions in Black–White health disparities require a better understanding of the mechanisms whereby lower income and education are associated with functional outcomes in older persons.